PERSEPSI KEPENTINGAN KONTEN PEMBELAJARAN DAN PENGUASAAN APLIKASI DALAM MATAKULIAH SISTEM INFORMASI AKUNTANSI - Pambudi, Rilo; Imbiri, Weli; Marsudi, Almatius Setya (Widya Mandala Surabaya Catholic University, 2020)
The purpose of this study is to determine whether there are differences in perceptions between lecturers, students, and companies regarding learning content and mastery of IT-based applications by Accounting students. Data collection was carried out by a survey using a questionnaire to accounting students, accounting teachers, and practitioners in the field of accounting about the importance of mastering IT-based applications and Accounting Information Systems course content for accounting graduates. Data analysis using descriptive analysis, and different tests. A different test is done by looking at the Chi-Square value in the SPSS program. The results show that perceptions of the importance of learning content for student respondents and lecturer respondents vary. While the results of the perception of the importance level of learning content for lecturer respondents and company respondents indicate there are differences for some items. The results for students' mastery of Information Technology applications show that there is a difference in perception about the needs of IT equipment by companies with lecturers on the Spreadsheet application.